Parenthesis and Ellipsis 2015
DOI: 10.1515/9781614514831.109
|View full text |Cite
|
Sign up to set email alerts
|

Parentheticals are – presumably – CPs

Abstract: This paper is concerned with the internal syntax of parentheticals in German. I argue that, despite superficial appearance, parentheticals form a categorially homogeneous class with respect to their category, namely they are clausal (i.e. CPs) throughout. To derive the fact that parentheticals show up as various categories at the surface, I adopt a movement plus deletion approach that assimilates parentheticals to other phenomena analysed as ellipsis, such as sluicing, fragment answers, split questions, amalga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…While these constructions do not fall under the traditional definition of apposition, they bear obvious parallels to bona fide NAPs owing to their reformulative character. This is also recognized by Heringa (2012a: 20), based on related discussion in del Saz Rubio (2003) and Jasinskaja (2009), and appears to be assumed by Döring's (2014) general approach to parentheticals. Despite these obvious extensions, I continue to restrict my focus to conventional cases of apposition in what follows, in order to keep the discussion within manageable proportions.…”
Section: Parallelism In R-napsmentioning
confidence: 66%
“…While these constructions do not fall under the traditional definition of apposition, they bear obvious parallels to bona fide NAPs owing to their reformulative character. This is also recognized by Heringa (2012a: 20), based on related discussion in del Saz Rubio (2003) and Jasinskaja (2009), and appears to be assumed by Döring's (2014) general approach to parentheticals. Despite these obvious extensions, I continue to restrict my focus to conventional cases of apposition in what follows, in order to keep the discussion within manageable proportions.…”
Section: Parallelism In R-napsmentioning
confidence: 66%
“…Because this structure is semantically identical to the host clause, as otherwise ellipsis would not be legitimate, an illusory effect obtains that there is actual c-command between the clause we see and the CLLDed phrase. The biclausal approach is therefore compatible with Döring's (2015) claim that all parentheticals are CPs.…”
Section: Interim Summarymentioning
confidence: 65%
“…I argue that in order to account for the data in the previous section, we must pay attention to their internal syntax. In particular, I contend, following Döring (2015) and Ott (2015), among others, that CLLDed phrases constitute an underlyingly bisentential structure where clausal ellipsis takes place in one of the two semantically identical clauses. The example in (33) would be analyzed as in (34) The two clauses are subject to a two-fold endophoric link, which is graphically illustrated in (35) (from Ott 2015: 239): the clitic, which is regarded as a free pro-form under the present approach, relates anaphorically to the dislocated phrase.…”
Section: The Biclausal Approachmentioning
confidence: 99%
“…2. In addition, ellipsis seems to be an important phenomenon in parenthetical constructions, as recent studies have shown (Döring 2015;Ott & Onea 2015;Ott 2016b;Stowell 2017).…”
Section: Syntactico-centric Approachesmentioning
confidence: 99%
“…On the other hand, one could also view the contrast above as a requirement on the antecedent of the elliptical parenthetical, but, under this perspective, the antecedent would be the string of the host clause preceding the parenthetical and not the entire host clause, as it is usually assumed (Ott 2016b;Stowell 2017;Ott & Onea 2015). In any case, the study of ellipsis in parentheticals is another fruitful research field (see specially Döring 2015) and deserves further attention. For instance, assuming that all parentheticals have a hidden clausal structure (as proposed in Döring 2015) has one welcome consequence: their prosodic isolation receives a natural explanation, since it is standard to assume that (root) CPs are mapped into intonational phrases in the syntax-phonology interface (Nespor & Vogel 1986;Selkirk 1981 et seq.…”
Section: An Interface-based Approach To Parentheticals: Multiple Spelmentioning
confidence: 99%